METODE TEPAT GUNA MENULIS ILMIAH BAGI SANTRI PONDOK PESANTREN AL ITQON DAN THOLABA BAROKATIL QURAN KOTA SEMARANG - Harjito .; Nazla Maharani Umaya; Ika Septiana (E-Dimas: Jurnal Pengabdian kepada Masyarakat, 2015)
Abstract This community services in the term of developing writing skills for Santri were conducted at two Islamic Boarding Schools: Al-Itqon and Tholaba Barokatil Qur?óÔé¼Ôäóan in Semarang city. The aim of this community services is developing thinking skills and writing skills for the Islamic boarding school community. The activities is in cooperation with the head of the Islamic Boarding School, taken place for nine months, in the form of on training, guidance, mentoring, and competition. The products are published on Bunga Rampai books with the approval numbers (ISBN 978-602-8047-07-9). The target of the program is increasing the Santri?óÔé¼Ôäós creativity on thinking and writing. Key word: Santri, thinking skills and writing skills